Metabolism and Autoimmune Responses: The microRNA Connection - Colamatteo, Alessandra; Micillo, Teresa; Bruzzaniti, Sara; Fusco, Clorinda; Garavelli, Silvia; De Rosa, Veronica; Galgani, Mario; Spagnuolo, Maria Immacolata; Di Rella, Francesca; Puca, Annibale A.; de Candia, Paola; Matarese, Giuseppe (Frontiers in Immunology, 2019)
Distinct metabolic pathways are known to regulate growth, differentiation, survival and activation of immune cells by providing energy and specific biosynthetic precursors. Compelling experimental evidence demonstrates that effector T cell functions are coupled with profound changes in cellular metabolism. Importantly, the effector T cell-dependent “anti-self” response characterizing the autoimmune diseases is accompanied by significant metabolic alterations. MicroRNAs (miRNAs), evolutionary conserved small non-coding RNA molecules that affect gene expression by binding to target messenger RNAs, are now known to regulate multiple functions of effector T cells, including the strength of their activation, thus contributing to immune homeostasis. In this review, we will examine the most recent studies that describe miRNA direct involvement in the metabolic reprogramming that marks effector T cell functions. In particular, we will focus on the work showing a connection between miRNA regulatory function and the molecular network dysregulation that leads to metabolic pathway derangement in autoimmunity. Finally, we will also speculate on the possibility that the interplay between miRNAs and metabolism in T cells may help identifying novel miRNA-based therapeutic strategies to treat effector T cell immunometabolic alterations in pathological conditions such as autoimmunity and chronic inflammation.